Mark Twain in Japan : the cultural reception of an American icon - Ishihara, Tsuyoshi, 1971- (University of Missouri Press, 2005)
"Explores the history of Mark Twain's reception in Japan in the spheres of books, children's magazines, and anime, the impact of Japanese translations on Twain's public image, how Japanese culture has transformed Japanese versions of Twain's works, and how Japan is culturally influenced by America and America by Japan"--Provided by publisher
Keywords: Twain, Mark, -- 1835-1910 -- Appreciation -- Japan.; Twain, Mark, -- 1835-1910 -- Translations into Japanese -- History and criticism.; Twain, Mark, -- 1835-1910; American literature -- Appreciation -- Japan.; Japanese literature -- American influences.; Books and reading -- Japan -- History.; Criticism -- Japan -- History.; Littérature américaine -- Appréciation -- Japon.; Littérature japonaise -- Influence américaine.; Livres et lecture -- Japon -- Histoire.; Critique -- Japon -- Histoire.; LITERARY CRITICISM -- American -- General.; American literature -- Appreciation; Art appreciation; Books and reading; Criticism; Japanese literature -- American influences; Japan; Criticism, interpretation, etc.; History